Laboratory Aspect of Broken Heart Syndrome - Y. Kusumo Adi Arji Atmanto; Sulina Yanti Wibawa; Darmawaty E Rauf (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Broken Heart Syndrome (BHS) is the weakness of the heart muscle due to emotional stress or physical stress called cardiomyopathy.  The main etiology is a sudden release of stress hormones (catecholamines), such as norepinephrine, epinephrine, and dopamine. About 90% of BHS patients are female with average age of 67-70"‰ years, most of them are post-menopausal females. The most widely supported pathological theories are catecholamine-induced cardiotoxicity and microvascular dysfunction. The clinical condition resembles that of acute myocardial infarction, consisting of chest pain, electrocardiographic changes, elevated cardiac biomarkers, and abnormalities of heart wall motion. There is transient systolic dysfunction in the apical and/or middle segment of the left ventricle resembling acute myocardial infarction but absence of coronary artery obstructive disease. There are BHS criteria according to Mayo Clinic. Laboratory tests can be performed by examining Natriuretic Peptides, cardio myonecrosis markers (Troponin I and T, creatinine kinase, and myoglobin), and catecholamines. There is no single established biomarker for initial diagnosis of BHS that distinguishes it from STEMI. It was found that the most accurate ratio as a marker capable of differentiating BHS from STEMI in early stages was NTproBNP/TnI ratio. The InterTAK diagnostic score was used to predict the probability of BHS, differentiating it from ACS in an acute stage, prior to coronary angiography. The main differential diagnosis of BHS is ACS, besides acute myocarditis infectious. Patients with BHS should be treated as ACS until proven otherwise. The prognosis for BHS patients is generally very good.